2014
DOI: 10.24297/jssr.v3i1.6665
|View full text |Cite
|
Sign up to set email alerts
|

Optimal inventory control for ameliorating, deteriorating items under time varying demand condition

Abstract: In this paper we discuss the development of an inventory model for ameliorating items such as fast growing animals like duck, pigs, broiler  in poultry farm, high-bred fishes with instantaneous replenishment  for the above type of items under cost minimization. A time varying type of demand rate with infinite time horizon, constant deterioration and without shortage is considered for the model. The result is illustrated with numerical example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Recently, the authors like Khan et al [ 10 ], Kumar et al [ 12 – 14 ], Li et al [ 16 ], Nayak et al [ 21 ], Samadi et al [ 24 ], Taleizadeh [ 27 ], Zang et al [ 29 ], and Zou and Tian [ 30 ] obtained optimal strategies for their inventory problems having zero lead time. Furthermore, we refer the interested readers to the works of Barik et al [ 1 ], Mishra et al [ 19 , 20 ], Routray et al [ 23 ], Singh et al [ 26 ] and Yu [ 28 ] for the inventory models having zero lead-time. However, Braglia et al [ 2 ], Kouki et al [ 11 ], Rahdar et al [ 22 ], Maiti et al [ 17 ], and Li [ 15 ] found the optimal strategies for retailer’s inventory problem with various positive lead-time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, the authors like Khan et al [ 10 ], Kumar et al [ 12 – 14 ], Li et al [ 16 ], Nayak et al [ 21 ], Samadi et al [ 24 ], Taleizadeh [ 27 ], Zang et al [ 29 ], and Zou and Tian [ 30 ] obtained optimal strategies for their inventory problems having zero lead time. Furthermore, we refer the interested readers to the works of Barik et al [ 1 ], Mishra et al [ 19 , 20 ], Routray et al [ 23 ], Singh et al [ 26 ] and Yu [ 28 ] for the inventory models having zero lead-time. However, Braglia et al [ 2 ], Kouki et al [ 11 ], Rahdar et al [ 22 ], Maiti et al [ 17 ], and Li [ 15 ] found the optimal strategies for retailer’s inventory problem with various positive lead-time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the exponentially declining demand for an inventory of imperfect quality havin constant deterioration was earlier taken into account by Jaggi et al [17]. For different inventory models with different demand and deteriorations under various inventory constraints, the attention of interested readers is drawn towards the works of Barik et al [1,2], Routray et al [37], and Mishra et al [28][29][30][31].…”
Section: Literature Reviewmentioning
confidence: 99%